Seven Memos for the future of the Mexican Stroke Association (Ictus, 2022)
Editorial presented by the President of AMEVASC Dr. Juan Manuel Calleja-Castillo for issue 3 number 3 of ICTUS, Journal of the Mexican Stroke Association.
Keywords: editorial; stroke; AMEVASC